2017
DOI: 10.1001/jama.2017.16378
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Denervation for Chronic Low Back Pain

Abstract: UCB]), for serving as project coordinator, a role for which she was compensated; and to Colleen Hoff, PhD (San Francisco State University [SFSU]), for her role in developing the study;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…However, among the studies which showed negative results, Juch et al 61 included 251 patients with 126 patients in the control group. Even though the study had a variety of limitations, [71][72][73][74][75][76][77][78] it is considered as one of the important studies in the literature. A second high-quality trial also showed lack of significant improvement with radiofrequency neurotomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, among the studies which showed negative results, Juch et al 61 included 251 patients with 126 patients in the control group. Even though the study had a variety of limitations, [71][72][73][74][75][76][77][78] it is considered as one of the important studies in the literature. A second high-quality trial also showed lack of significant improvement with radiofrequency neurotomy.…”
Section: Discussionmentioning
confidence: 99%
“… 125 In conclusion, the longer the time as well as the higher the temperature, the radiofrequency lesion size will be bigger, and there could be a difference in radiofrequency lesion size due to needle size and placement of radiofrequency denervation. 89 , 116 , 126 …”
Section: Managementmentioning
confidence: 99%
“…Once the aforementioned Juch et al MINT trial results were published in JAMA , that journal published a series of three letters to the editor18–20 and a response by MINT trial coauthors Maas, Juch, and Huygen,21 as is appropriate and customary. However, elsewhere, other authors and other journals have published criticisms of the Juch et al report, absent a response from the MINT trial authors 22 23.…”
Section: Casting a Broader Netmentioning
confidence: 99%